2012
DOI: 10.1021/jf302931z
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizing Soil with Selenium Fertilizers: Impact on Concentration, Speciation, and Bioaccessibility of Selenium in Leek (Allium ampeloprasum)

Abstract: Leek was fertilized with sodium selenite (Na(2)SeO(3)) and sodium selenate (Na(2)SeO(4)) in a green house to assess the impact of selenium (Se) fertilization on Se uptake by the crop and its speciation in the crop. The bioaccessibility of Se in the Se-enriched leek was assessed using an in vitro extraction protocol mimicking the human gastrointestinal tract (stomach, small intestine, and colon). The lowest Se uptake was observed when Na(2)SeO(3) was used as a fertilizer, which results in a higher risk for Se a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 31 publications
(40 reference statements)
6
32
1
Order By: Relevance
“…Furthermore, we observed that Se content in garlic plants was increased thirty times by Se fertilization (Table 2). Similar results have been reported for other Allium plants like ramps, leek and onion where Se accumulation was also around 1000 µg g -1 (Montes- Bayón et al, 2002;Lavu et al, 2012;Schiavon & Pilon-Smits, 2017). For this reason, the Allium plants are considered as Se hyperaccumulaters and represent natural Se sources to humans.…”
Section: Accumulation Of Se In Different Garlic Organssupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, we observed that Se content in garlic plants was increased thirty times by Se fertilization (Table 2). Similar results have been reported for other Allium plants like ramps, leek and onion where Se accumulation was also around 1000 µg g -1 (Montes- Bayón et al, 2002;Lavu et al, 2012;Schiavon & Pilon-Smits, 2017). For this reason, the Allium plants are considered as Se hyperaccumulaters and represent natural Se sources to humans.…”
Section: Accumulation Of Se In Different Garlic Organssupporting
confidence: 84%
“…Four doses were applied: 0, 5, 10 and 15 kg ha -1 of Se, with a random plot design and three replicates. The tested Se doses were similar to those reported in other studies about the Allium gender (Sharma et al, 2007;Domokos-Szabolcsy et al, 2011;Lavu et al, 2012). Three samplings were performed: at the beginning (September 2014:103-BBCH), mid-term (October 2014; 203-BBCH scale) and end (December 2014; 409-BBCH scale) of the growth cycle (Lopez-Bellido et al, 2016).…”
Section: Cultivation Of Se Enriched Garlicsupporting
confidence: 52%
See 1 more Smart Citation
“…The same trend is observed for seeds, usually consumed by human organisms, but results are here not significant. By contrast, working on Se oral bioaccessibility in leek (Allium ampeloprasum), Lavu et al (2012) highlighted that in the gastric phase, Se bioaccessibility was slightly higher when the leek was grown on selenite-enriched soil (63 %), as compared to selenate-enriched soil (56 %), although this difference is not significant. In our study, there is no significant difference in selenate bioaccessible fraction in function of the maize tissue, i.e., stems, leaves, or seeds.…”
Section: Selenium Gastric Bioaccessibility (Gb) In Maizementioning
confidence: 97%
“…Therefore, it is considered as a high commercial value element. In agriculture, selenium has been applied as fertiliser in selenium deficient regions (Lavu et al, 2012) and has also been used to inhibit the formation of sulfate-mediated methylmercury in paddy fields, wherein amendment of selenium in soil leads to the formation of stable and non-toxic Hg-Se complex(es) . Being an essential element, selenium intake is recommended via food supplements in order to avoid deficiency in humans and animals (Rautiainen et al, 2016).…”
Section: Selenium (Sementioning
confidence: 99%